Photochromism of the complex between 4'-(2-hydroxyethoxy)-7-hydroxyflavylium and beta-cyclodextrin, studied by H-1 NMR, UV-Vis, continuous irradiation and circular dichroism - Gago, Sandra; Basilio, Nuno; Fernandes, Ana; Freitas, Victor; Quintas, Alexandre; Pina, Fernando (Dyes and Pigments, 2014)
n/a
Basilio, Nuno/F-2389-2012; Pina, Fernando/C-8161-2011; Gago, Sandra/H-5413-2012 Basilio, Nuno/0000-0002-0121-3695; Pina, Fernando/0000-0001-8529-6848; Gago, Sandra/0000-0003-0221-8508 Si 1